2016
DOI: 10.1016/j.parkreldis.2015.08.036
|View full text |Cite
|
Sign up to set email alerts
|

Functional (psychogenic) movement disorders – Clinical presentations

Abstract: Functional or psychogenic movement disorders are common and disabling, and sometime difficult to diagnose. The history and physical exam can give positive features that will support the diagnosis, which should not be based solely on exclusion. Some clues in the history are sudden onset, intermittent time course, variability of manifestation over time, childhood trauma, history of other somatic symptom and secondary gain. Anxiety and depression are common, but not necessarily more than the general population. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
80
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 25 publications
1
80
0
2
Order By: Relevance
“…The authors suggested that movement avoidance may have been adopted to avoid pain, and in time resulted in fixed dystonia. The etiology of the fixed dystonia has also been variously attributed to peripheral injury [van Rooijen et al, ], and psychogenic movement disorder [Hallett, ].…”
Section: Dystonias and Other Movement Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors suggested that movement avoidance may have been adopted to avoid pain, and in time resulted in fixed dystonia. The etiology of the fixed dystonia has also been variously attributed to peripheral injury [van Rooijen et al, ], and psychogenic movement disorder [Hallett, ].…”
Section: Dystonias and Other Movement Disordersmentioning
confidence: 99%
“…Neurological evaluation and EEG to rule out seizure should be performed. The diagnosis of psychogenic movement disorder has been met with some skepticism [Palmer et al, ], but is distinguished from malingering, and thought to result from psychological causes [Hallett, ]; it is characterized by involuntary, disabling movements, abrupt in onset, a waxing/waning course, changes in the nature of the movement over time, worsening with stress, anxiety or depression, and improvement with distraction; they are difficult to diagnose and treat. Prognosis for improvement is better in patients with a shorter duration of illness [Lang, ].…”
Section: Dystonias and Other Movement Disordersmentioning
confidence: 99%
“…The cause of hyperhidrosis in our patient is not clear, and we speculate that it was another functional symptom. Our case reiterates that careful history taking and physical/neurologic examination are key to ascertaining the correct diagnosis in patients with functional movement disorders and that sometimes laboratory findings, such as KFS in our patient, can be misleading.…”
Section: Discussionmentioning
confidence: 53%
“…27 Some of the positive criteria that help define psychogenic tremor and other functional movement disorders are listed in ►Table 9. 28 Functional tremors are often entrainable (brought to a specific rhythm). This can be demonstrated by having the patient tap the hand or flex and extend the wrist of the opposite hand at various frequencies.…”
Section: Functional /Psychogenic Movement Disordersmentioning
confidence: 99%